Potential Impact of B Cells on T Cell Function in Multiple Sclerosis. (27th February 2011) - Ireland, Sara; Monson, Nancy
Abstract : Multiple sclerosis is a chronic debilitating autoimmune disease of the central nervous system. The contribution of B cells in the pathoetiology of MS has recently been highlighted by the emergence of rituximab, an anti-CD20 monoclonal antibody that specifically depletes B cells, as a potent immunomodulatory therapy for the treatment of MS. However, a clearer understanding of the impact B cells have on the neuro-inflammatory component of MS pathogenesis is needed in order to develop novel therapeutics whose affects on B cells would be beneficial and not harmful. Since T cells are known mediators of the pathology of MS, the goal of this review is to summarize what is known about the interactions between B cells and T cells, and how current and emerging immunotherapies may impact B-T cell interactions in MS.